Analysis of the Effect of Cash Ratio on Corporate Bankruptcy Risk: Case Study of Manufacturing Companies - Tenripada, Andi Sakinah Yan; Wandira, Ika (Operations Research: International Conference Series, 2025)
This study aims to explore the relationship between cash ratio and bankruptcy risk using an empirical analysis approach, and relate it to the Altman Z-score model as an indicator of financial sustainability. By analyzing the financial statement data of companies listed on the stock exchange during the period 2019-2023, this study investigates the impact of liquidity measured by cash ratio on bankruptcy potential. Regression method is used to assess the relationship, while Altman Z-score serves as a tool to measure the financial health of the company. The results show that the cash ratio contributes little to reducing the risk of bankruptcy, yet firms with higher liquidity exhibit a better Z-score. These findings highlight the importance of liquidity management as a strategy to ensure the financial sustainability of firms in the face of bankruptcy challenges.